Efforts in Finding and Maintaining Business in the New Normal Era - Ibrahim Reyhan Nugraha Putra Reyhan; Ifah Nur Faizah; Sheila Febriani Putri (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This research was conducted to answer what business actors can do to be able to maintain their business amid the COVID-19 pandemic that is sweeping the world. This study also aims to describe what are the survival strategies that must be carried out by business actors. Therefore, they can survive and become more responsive and adaptable to business changes, especially during the current COVID-19 pandemic. Usually, even though there are online sales, many consumers still buy products directly at the store or shopping center. The research method used in this research is descriptive qualitative which is the right type of research to capture human perception with direct contact through an inductive process and symbolic interaction. Using literature review, the decomposition of the data was obtained. This research provides an opinion in finding opportunities and maintaining business in the new normal era for MSME in the form of recognizing consumer behavior, improving quality and services, using technology in MSME in the form of digital marketing, building synergies between digital MSME and citizens, and use the Customer relationship marketing (CRM).